Pengaruh Konsep Diri dan Sikap Mahasiswa pada Matematika terhadap Hasil Belajar Mata Kuliah Matematika Dasar - Nurma Tambunan (JKPM (Jurnal Kajian Pendidikan Matematika), 2016)
This research is aimed to acknowledging the impacts of both self concept and student’s attitude toward mathematics  on the result of learning mathematics . The method used in this research is corrasional survey methode. Sample in this research is taken from affordable population by using simple random sampling from the number of population reach as many as 98 respondents. The instrument used is questionnaire on variables of self concept and student’s attitude on mathematics  and test instrument on variables of the result of learning mathematics . After all instrument valid and reliable, the data was analyzed descriptively after the data fulfill normality test and linnearity test and the result show that distribution of the data is normal and the pattern of regression is linear. So the analysis is continued to statistic parametric analysis. Actually the research used double regression analysis. The result show that in simultaneous  self concept and student’s attitude on mathematics give positive impacts and significant impacts on the result of learning mathematics with regression equation Y = 39,653 X1 + 0,0045 X2. It means that if self concept and student’s attitude was good on mathematics, so the result of learning mathematics was good.